Product development from mudskipper and giant snakehead fish oils - Omar, Muhammad Nor; Zainuddin, Nur Aziyah; Mohamad Talib, Hasan; Zuberdi, Ahmad Muzammil; Yunus, Kamaruzzaman (2010)
Several products from mudskipper and giant snakehead oil were developed. The topical creams were produced in the form of water-in-oil emulsions. The creams are suitable for pharmaceutical uses such as reducing rheumatoid arthritis and would healing. Other products in the forms of soft gels and capsules could be used as food supplements.